2019
DOI: 10.3390/agronomy9090534
|View full text |Cite
|
Sign up to set email alerts
|

Is Cattle Manure Application with Plastic-Film Mulch a Good Choice for Potato Production?

Abstract: Using manure in potato production has been considered for its potential environmentally friendly effects. Two years of field experiments were conducted to evaluate the effects of different kinds of fertilizer and soil surface treatments on potato growth. Experimental treatments consisted of three soil surface treatments, including black plastic-film mulch (BM), transparent film-plastic mulch (TM), and non-mulched (NM) treatment, and two fertilizer treatments, including inorganic fertilizer (IF), and cattle man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Soil matric potential (SMP) is a useful criterion for characterizing crop soil water availability, and SMP-based drip irrigation management has been successfully applied to improve yields in many crops [24][25][26][27][28][29]. The SMP threshold for quinoa drip irrigation scheduling can vary with soil texture, active rooting depth of quinoa, planting configuration, water availability for irrigation, and many other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Soil matric potential (SMP) is a useful criterion for characterizing crop soil water availability, and SMP-based drip irrigation management has been successfully applied to improve yields in many crops [24][25][26][27][28][29]. The SMP threshold for quinoa drip irrigation scheduling can vary with soil texture, active rooting depth of quinoa, planting configuration, water availability for irrigation, and many other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Soil moisture was another primary factor affecting N 2 O emissions. MC treatment could significantly increase soil moisture, which has been reported by lots of studies [ 8 , 21 ]. We also found soil N 2 O emissions had a positive correlation with WFPS (from 39% to 62%) ( Figure 2 ), which was consistent with that of Zhao [ 10 ].…”
Section: Discussionmentioning
confidence: 72%
“…This study showed a negative impact of MC treatment on greenhouse gas mitigation. On the other hand, studies have reported a significant positive effect of MC treatment on potato harvest [ 8 ]. Therefore, further research should be devoted to examining the impacts of MC treatment on both potato harvests and N 2 O emissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations